The Predictive Value of Glucagon-Like Peptide 1 Plasma Levels on Acute Heart Failure - Muhamad Firman Wahyudi; JB. Suparyatmo; Dian Ariningrum (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2022)
Acute Heart Failure (AHF) is one of the mechanical complications of Acute Myocardial Infarct (AMI). The diagnostic approach of AHF caused by AMI is based on clinical score, imaging, use of invasive instruments, and laboratory parameters. Glucagon-Like Peptide-I (GLP-1) is an incretin hormone derivate of proglucagon gene transcription, secreted by the L cells from the mucosa of the ileum, colon, and rectum. The cardioprotective effect of GLP-1 through the dependent and independent pathway produces a direct and indirect cardiovascular effect that increases the functional capacity in AHF patients. This study aims to find the predictive value of plasma GLP-1 towards the incidence of AHF in patients with AMI. This study was conducted on 35 patients diagnosed with AMI at Dr. Moewardi General Hospital Surakarta, in October-December 2020. Glucagon-like peptide-I was measured using the ELISA sandwich. The cut-off of plasma GLP-1 was determined using the Receiver Operating Characteristic (ROC) curve. Statistical analysis showed an RR (95% CI) of 2.292 (0.587–8.943) with a p=0.229 for age, 1,143 (0.299–4.367) with a p – 0.127 for a history of type 2 diabetes (T2DM) and plasma GLP-1 concentrations below Cut-Off Value (COV), which was 2.881 (0.729–11.381) with p=0.127. Age, a history of T2DM, and plasma GLP-1 below COV did not significantly affect AHF complications in patients with AMI.